An Update on Physician Practice Cost Shares - Dayhoff, Debra A. (CENTERS for MEDICARE & MEDICAID SERVICES, 1993)
The 1988 physicians' practice costs and income survey (PPCIS) collected detailed costs, revenues, and incomes data for a sample of 3,086 physicians. These data are utilized to update the Health Care Financing Administration (HCFA) cost shares used in calculating the medicare economic index (MEI) and the geographic practice cost index (GPCI). Cost shares were calculated for the national sample, for 16 specialty groupings, for urban and rural areas, and for 9 census divisions. Although statistical tests reveal that cost shares differ across specialties and geographic areas, sensitivity analysis shows that these differences are small enough to have trivial effects in computing the MEI and GPCI. These results may inform policymakers on one aspect of the larger issue of whether physician payments should vary by geographic location or specialty.